INCREASING COMPETENCE OF PHARMACY AND PHARMACY TECHNICAL PERSONNEL IN DETECTING HARMFUL CONTENT IN SKIN CARE PRODUCTS - Riana Versita; Myran Nur Hinsany; Novi Yantih; Dwi Kurnia Putri; Dian handayani; Nori Wirahmi; Ikhsan, Ikhsan (Journal of Community Service, 2024)
Each skin care product has different active ingredients. In fact, Natural skin care products also contain their own active ingredients ingredients. The ingredients used in making skin care must pay attention to the safety of the user. This is not uncommon in skin care Products in circulation contain dangerous chemicals such as mercury, hydroquinone, speech, lead, etc. Pharmacy Technical personnel and pharmacists have an important role in this matter detecting harmful ingredients in skin care. Therefore, D3 Pharmacy Study Program, Faculty of Mathematics and Natural Sciences Bengkulu University of Science with Lentera Nakes as a form of community service, there is an online socialization of the National Pharmacy Seminar which will be held will be held on December 10, 2023 at 10.00 until it ends theme of Competency of Pharmaceutical Technical Personnel and Pharmacists in Detecting Dangerous Ingredients for Skin Care. This seminar can have a big impact on competency from the participants and understanding of dangerous ingredients in cosmetics